2019
DOI: 10.3390/min9060331
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Bioleaching of Phosphorus and Uranium

Abstract: Phosphorus and uranium are both vital elements for society. In recent decades, fears have arisen about the future availability of low-cost phosphorus and uranium. This has resulted in pressure to de-centralize production of both elements by utilizing lower-grade or complex deposits. The research presented here focused on phosphorus-containing apatite ores with uranium impurities; in order to separate uranium by selective and sequential bioleaching before phosphorus leaching. This would create an alternative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Commercial biomining applications have conventionally targeted copper, gold, uranium, nickel, cobalt and zinc [8]. More recently, the possibilities of extracting other commodities such as rare earth elements and phosphorus (P) have also been evaluated [9,10]. The cumulative number of publications listed in Scopus referring (in the title, abstract and/or keywords) to bioleaching, biooxidation, biomining or biosolubilisation, and copper, zinc, nickel, gold, cobalt, uranium or rare earths are shown in Figure 1B.…”
Section: Application Areasmentioning
confidence: 99%
“…Commercial biomining applications have conventionally targeted copper, gold, uranium, nickel, cobalt and zinc [8]. More recently, the possibilities of extracting other commodities such as rare earth elements and phosphorus (P) have also been evaluated [9,10]. The cumulative number of publications listed in Scopus referring (in the title, abstract and/or keywords) to bioleaching, biooxidation, biomining or biosolubilisation, and copper, zinc, nickel, gold, cobalt, uranium or rare earths are shown in Figure 1B.…”
Section: Application Areasmentioning
confidence: 99%
“…Bacterial leaching of metallic sulphides has developed quickly over the last few decades [ 25 ]. The utilization of microorganisms for the retrieval of heavy metals has become a well-established biotechnological practice [ 26 , 27 ], which has been used primarily in copper [ 25 , 28 , 29 ], cobalt [ 30 ], nickel [ 31 ], zinc [ 32 ], and uranium [ 33 ] recovery, metals that are typically obtained from sulfides that are insoluble or, in the case of uranium, from oxidized minerals [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known a number of studies devoted to the behavior of rare earth elements in phosphorite ores [1,2] and natural water [3][4][5]. It was investigated the possibility of rare earth elements composition obtaining from deposits in the Southwestern Sinai, the characterization of the residue shows the presence of uranium, rare-earth elements (REE), aluminum, and zinc that can be valorized [6].…”
Section: Introductionmentioning
confidence: 99%
“…An especially acute environmental problem arises in the presence of concomitant radioactive elements, which complicates the implementation of waste recycling processes. In studies by Mäkinen et al [2] the possibility of preliminary selective separation of uranium from phosphoruscontaining apatite ores with uranium impurities has been shown. It was found that the mixture used is fluorapatite and standard uranium ore and requires 24-hour sulfuric acid leaching at pH = 1 to obtain a 100% phosphorus yield.…”
Section: Introductionmentioning
confidence: 99%